2015
DOI: 10.18869/acadpub.ijal.18.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Proceduralization and Transfer of Linguistics Knowledge as a Result of Form-focused Output and Input Practice

Abstract: This study compared the effects of two types of form-focused tasks on proceduralization and transfer of linguistics knowledge in case of English modals. All participants of the study attended pretests, posttests and delayed posttests. The procedural comprehension and production knowledge were measured through the groups" performance on a timed dual task test that resembled the context of practice. The transfer of knowledge was measured by evaluating the performance of participants on a timed dual task test in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…That is, the results of this study suggest that if sufficient practice of different variety is provided, it helps foreign language learners develop receptive and productive modes of L2 knowledge. The results are in line with earlier findings that input‐based and output‐based practices result in the acquisition of both receptive and productive knowledge (Fakharzadeh & Youhanaee, 2015; Cerezo, Caras & Leow, 2016; Nazari, 2013; Yamashita & Iizuka, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…That is, the results of this study suggest that if sufficient practice of different variety is provided, it helps foreign language learners develop receptive and productive modes of L2 knowledge. The results are in line with earlier findings that input‐based and output‐based practices result in the acquisition of both receptive and productive knowledge (Fakharzadeh & Youhanaee, 2015; Cerezo, Caras & Leow, 2016; Nazari, 2013; Yamashita & Iizuka, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…This study investigated the effect of input-based practice and output-based practice on the acquisition of complex English infinitival structures. The results showed that there were significant differences between participants' perfor- based practices result in the acquisition of both receptive and productive knowledge (Fakharzadeh & Youhanaee, 2015;Cerezo, Caras & Leow, 2016;Nazari, 2013;Yamashita & Iizuka, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations